Antibiotics for lower respiratory tract infection in children presenting in primary care (ARTIC-PC): the predictive value of molecular testing. (September 2022) - Little, Paul; Read, Robert C.; Becque, Taeko; Francis, Nick A.; Hay, Alastair D.; Stuart, Beth; O'Reilly, Gilly; Thompson, Natalie; Hood, Kerenza; Faust, Saul; Wang, Kay; Moore, Michael; et al.
Abstract: Objectives: This study aimed to assess whether the presence of bacteria or viruses in the upper airway of children presenting with uncomplicated lower respiratory tract infection (LRTI) predicts the benefit of antibiotics. Methods: Children between 6 months and 12 years presenting to UK general practices with an acute LRTI were randomized to receive amoxicillin 50 mg/kg/d for 7 days or placebo. Children not randomized (ineligible or clinician/parental choice) could participate in a parallel observational study. The primary outcome was the duration of symptoms rated moderately bad or worse. Throat swabs were taken and analyzed for the presence of bacteria and viruses by multiplex PCR. Results: Swab results were available for most participants in the trial (306 of 432; 71%) and in the observational (182 of 326; 59%) studies. Bacterial pathogens potentially sensitive to amoxicillin ( Haemophilus influenzae, Moraxella catarrhalis, Streptococcus pneumoniae ) were detected among 51% of the trial placebo group and 49% of the trial antibiotic group. The median difference in the duration of symptoms rated moderately bad or worse between antibiotic and placebo was similar when potentially antibiotic-susceptible bacteria were present (median: –1 day; 99% CI, –12.3 to 10.3) or not present (median: –1 day; 99% CI, –4.5 to 2.5). Furthermore, bacterial genome copy number did not predict benefit. There were similar findings for all secondary outcomes and when including the data from the observational study. Discussion: There was no clear evidence that antibiotics improved clinical outcomes conditional on the presence or concentration of bacteria or viruses in the upper airway. Before deploying microbiologic point-of-care tests for children with uncomplicated LRTI in primary care, rigorous validating trials are needed.